Reconfigurable engineered motile semiconductor microparticles - Ugonna Ohiri; C. Wyatt Shields; Koohee Han; Talmage Tyler; Orlin D. Velev; Nan Jokerst (Nature Communications, 2018)
Active particles that demonstrate life-like behavior may find use in bio-inspired technologies, but achieving on-demand reconfiguration remains challenging. Here, the authors demonstrate controllable, collective behavior in silicon microparticles, which are fabricated via conventional semiconductor methods.